The highly sensitive parent eaudiobook Be brilliant in your role, even when the world overwhelms you. - Aron, Elaine N. (Recorded Books Inc., 2020)
First, she taught you the value of your highly sensitive nature in her bestselling classic The Highly Sensitive Person. Now, Dr. Elaine Aron is back to teach you how to utilize your sensitivity to tackle a new challenge: Parenthood. Parenting is the most valuable and rewarding job in the world, and also one of the most challenging. This is especially true for highly sensitive people. Highly sensitive parents are unusually attuned to their children. They think deeply about every issue affecting their kids and have strong emotions, both positive and negative, in response. For highly sensitive people, parenting offers unique stresses—but the good news is that sensitivity can also be a parent's most valuable asset, leading to increased personal joy and a closer, happier relationship with their child. Dr. Elaine Aron, world-renowned author of the classic The Highly Sensitive Person and other bestselling books on the trait of high sensitivity, has written an indispensable guide for these parents. Drawing on extensive research and her own experience, she helps highly sensitive parents identify and address the implications of their heightened sensitivity, offering: A self-examination test to help parents identify their level of sensitivity Tools to cope with overstimulation Advice on dealing with the negative feelings that can surround parenting Ways to manage the increased social stimulation and interaction that comeswith having a child Techniques to deal with shyness around other parents Insight into the five big problems that face highly sensitive parents in relationships—and how to work through them Highly sensitive people have the potential to be not just good parents, but great ones. Practical yet warm and positive, this groundbreaking guide will show parents how to build confidence, awareness, and essential coping skills so that they—and their child—can thrive on every stage of the parenting journey.